Residue soil type construction waste regenerated pervious concrete and preparation method thereof

By using recycled slag aggregates and a variety of modified materials in permeable concrete, the existing permeable concrete has been solved, and the high strength, crack resistance, permeability and self-repair effect has been achieved. , adapt to complex environmental needs, extend service life and improve urban drainage pressure.

CN119161149AInactive Publication Date: 2024-12-20禹智环保科技(深圳)有限公司

Patent Information

Application Number
CN202411357788.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing permeable concrete is inefficient in utilizing construction waste, lacks performance, and lacks self-repair and versatility, making it difficult to meet the complex environment and high-demand engineering needs.

Method used

Use recycled residue aggregate, nanosilicon sol, bio-based reinforcement, magnesium-aluminum spinel micropowder, nanocarbon tubes, composite water reducing agent, reinforcement fiber, nanotitanium dioxide, zeolite powder, magnetic adsorption particles and self-healing microcapsules. The components are formed by multi-stage crushing, screening and modification treatment to form highly efficient, water-permeable, crack-resistant, self-repaired concrete.

Benefits of technology

It significantly improves the strength, crack resistance and water permeability of concrete, realizes the recycling of resources, reduces production costs, has self-repair and pollutant adsorption functions, adapts to complex environmental needs, extends service life and improves urban drainage pressure .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161149A_ABST
    Figure CN119161149A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and discloses residue soil type construction waste regenerated pervious concrete and a preparation method thereof.The residue soil type construction waste regenerated pervious concrete is prepared from 850-1250 parts of regenerated residue soil aggregate, 220-380 parts of cement, 60-110 parts of fly ash, 25-55 parts of silica fume, 4-9 parts of a water reducing agent, 6-18 parts of reinforced fibers, 3-7 parts of a pervious additive and 4-9 parts of nano titanium dioxide; the self-repairing coating is prepared from, by weight, 12-35 parts of zeolite powder, 35-65 parts of superfine slag powder, 5-10 parts of magnetic adsorption particles and 3-8 parts of self-repairing microcapsules. By adding the reinforced fibers, the compressive strength is improved, the crack risk is reduced, the permeation coefficient is improved by adding the permeation accelerant, the drainage pressure is relieved, the self-repairing efficiency is improved by utilizing the self-repairing microcapsules, the magnetic adsorption particles are added, the water environment is improved, the composite water reducing agent is adopted, the cost is reduced, and the durability is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, in particular to a kind of regenerated permeable concrete of muck-type construction waste and a preparation method thereof. Background Art

[0002] With the acceleration of urbanization and the continuous advancement of infrastructure construction, the construction industry has flourished, but at the same time, a large amount of construction waste has been generated. As an important component of this, the amount of construction waste such as slag is increasing day by day. The traditional treatment method is mainly to simply landfill or pile it up, which not only occupies a large amount of land resources, but also has many negative impacts on the environment, such as soil pollution, groundwater pollution, and affecting the surrounding ecological landscape. Moreover, with the increasing tension of urban land resources, this extensive treatment method is no longer sustainable.

[0003] In urban construction, the hardened area of ​​the ground is constantly increasing, resulting in a sharp decline in the natural infiltration capacity of rainwater, which has brought great pressure to the urban drainage system. Whenever there is heavy rain, urban waterlogging problems frequently occur. Permeable concrete, as a new type of environmentally friendly building material, has good permeability, which can allow rainwater to quickly penetrate into the ground, replenish groundwater, relieve urban drainage pressure, and realize the natural circulation of rainwater. Therefore, its demand in ground paving projects such as urban roads, squares, and parking lots is growing.

[0004] There are some significant problems in the practical application of permeable concrete on the market. On the one hand, the aggregates used in ordinary permeable concrete are mostly conventional materials such as natural sand and gravel, and the utilization rate of construction waste is extremely low, which cannot effectively realize the recycling of resources. On the other hand, there are certain limitations in its performance. For example, its strength and durability are often difficult to meet some high-demand engineering application scenarios. It performs poorly in terms of crack resistance and is prone to cracks and other defects, which affect its service life and use effect. The stability and durability of permeability also need to be improved. As time goes by, the permeable pores are easily blocked, resulting in a gradual decline in permeability.

[0005] In addition, existing permeable concrete is relatively simple in functionality and lacks the ability to cope with complex environments and special needs. For example, in some urban areas with severe pollution, it cannot effectively absorb and degrade heavy metal ions and organic pollutants in rainwater, and its effect on improving the environment is limited. Moreover, when concrete is damaged by cracks, it cannot self-repair and requires a lot of manpower and material resources for repair.

[0006] In the face of the above problems, there is an urgent need to develop a new type of permeable concrete and its preparation method. This new type of permeable concrete should be able to make full use of construction waste such as slag, realize resource recycling and reuse, reduce production costs and reduce damage to the environment. And it needs to have a significant improvement in performance, with high strength, good crack resistance and stable permeability to meet the needs of various complex engineering environments. At the same time, it should also have a variety of additional functions, such as adsorption of pollutants, self-repair, etc., to improve its comprehensive application value and adaptability, and provide better solutions for urban construction and environmental protection. Summary of the invention

[0007] 1. Technical issues to be resolved

[0008] In view of the deficiencies in the prior art, the present invention provides a soil-type construction waste recycled permeable concrete and a preparation method thereof.

[0009] (II) Technical solution

[0010] A regenerated permeable concrete made of slag and construction waste, comprising the following components in parts by weight:

[0011] Recycled slag aggregate: 850 to 1250 parts, wherein the recycled slag aggregate is obtained by crushing, screening and strengthening treatment of slag construction waste, wherein the particle size of 5 mm to 10 mm accounts for 42% to 52%, the particle size of 10 mm to 20 mm accounts for 32% to 42%, and the particle size of 20 mm to 30 mm accounts for 12% to 22%. In the strengthening treatment of the recycled slag aggregate, nano-silica sol is used for surface impregnation treatment, the impregnation time is 1.2 hours to 2.2 hours, the solid content of the nano-silica sol is 12% to 22%, and a bio-based strengthener is used for secondary impregnation treatment, the bio-based strengthener is composed of chitosan, sodium lignin sulfonate and sodium alginate in a weight ratio of 2:1:1, and the impregnation time is 0.5 hours to 1 hour;

[0012] Cement: 220 to 380 parts, wherein the cement is mixed with 5 to 10% by weight of magnesium-aluminum spinel powder, the particle size of which is 1 to 5 microns, which can effectively improve the early strength and crack resistance of the cement;

[0013] Fly ash: 60 to 110 parts. The fly ash is treated with plasma modification at a power of 10 kW to 20 kW for 10 to 20 minutes to enhance its surface activity and improve its binding force with other components.

[0014] Silica fume: 25 to 55 parts, with 3 to 8% by weight of carbon nanotubes added to the silica fume. The length of the carbon nanotubes is 10 to 30 microns, and the diameter is 5 to 10 nanometers, which can enhance the electrical and thermal conductivity of concrete, while improving its mechanical properties;

[0015] Water reducer: 4 to 9 parts. The water reducer is a composite water reducer composed of polycarboxylic acid high-performance water reducer, lignin sulfonate water reducer and β-cyclodextrin grafted modified water reducer in a mass ratio of 5:2:1, and the water reduction rate is not less than 30%;

[0016] Reinforcement fiber: 6 to 18 parts, fiber length is 12 mm to 25 mm, the reinforcement fiber includes a mixed fiber composed of polypropylene fiber, basalt fiber and carbon fiber in a mass ratio of 3:2:1, and the carbon fiber is surface oxidized by soaking it in a 5 mol / L nitric acid solution for 1 to 2 hours, and then drying it at 80°C to 100°C, so that rich oxygen-containing functional groups are formed on its surface to improve the bonding strength with the concrete matrix;

[0017] Water permeability aid: 3 to 7 parts, the water permeability aid is composed of the following raw materials in parts by weight: 1.5 to 3.5 parts of organic silane coupling agent, 1.5 to 3.5 parts of surfactant, and 1 to 2 parts of a new type of nano-scale water permeability promoter. The nano-scale water permeability promoter is a zeolite molecular sieve with a special pore structure, with a pore size of 2 nanometers to 5 nanometers, which can form an efficient water permeable channel in the concrete;

[0018] Nano titanium dioxide: 4 to 9 parts. Nano titanium dioxide is a mixture of anatase and rutile in a mass ratio of 3:2. The particle size is 8 to 25 nanometers. It has undergone double surface modification treatment, first using a silane coupling agent for surface grafting treatment, and then using dopamine for coating, so that it has better dispersibility and photocatalytic performance;

[0019] Zeolite powder: 12 to 35 parts. The zeolite powder undergoes multi-stage activation treatment, first calcined at a high temperature of 400 to 600°C for 2 to 3 hours, and then treated at a microwave power of 500 to 800 W for 5 to 10 minutes, so that its pore structure is more developed and the adsorption performance is significantly enhanced;

[0020] Slag powder: 35 to 65 parts. The slag powder is ultra-finely ground to a particle size of no more than 5 microns, and 2 to 5% by weight of nano-alumina is added to the powder. The particle size of the nano-alumina is 10 to 20 nanometers, which can further improve the activity of the slag powder and the strength of the concrete.

[0021] Magnetic adsorption particles: 5 to 10 parts. The magnetic adsorption particles are composed of ferroferric oxide and activated carbon in a mass ratio of 3:2. The particle size is 0.5 mm to 2 mm. They can effectively adsorb heavy metal ions and organic pollutants in water and improve the environmental performance of concrete.

[0022] Self-repairing microcapsules: 3 to 8 parts. The wall material of the self-repairing microcapsules is urea-formaldehyde resin, and the core material is a mixture of epoxy resin and curing agent. When cracks appear in the concrete, the microcapsules rupture and release the repair material to achieve automatic repair function.

[0023] Preferably, the cement is silicate cement or ordinary silicate cement with a strength grade of not less than 42.5, and nano calcium hydroxide accounting for 0.5% to 1.5% by weight is added to the cement, and the particle size of the nano calcium hydroxide is 20 nanometers to 50 nanometers;

[0024] The polypropylene fiber in the reinforcing fiber is a modified polypropylene fiber, and an acrylic copolymer is grafted on its surface; the basalt fiber is treated with a surface silane coupling agent, the concentration of the treatment solution is 3% to 5%, and the treatment time is 0.5 hour to 1 hour;

[0025] The preparation method of the β-cyclodextrin grafted modified water reducer in the water reducer is: grafting β-cyclodextrin with acrylic acid under alkaline conditions with a pH value of 9 to 11, the reaction temperature is 50° C. to 70° C., the reaction time is 3 hours to 5 hours, and then compounding with a polycarboxylic acid high-performance water reducer and a lignin sulfonate water reducer;

[0026] The silane coupling agent grafted on the surface of the nano titanium dioxide is γ-aminopropyltriethoxysilane, the grafting rate is not less than 80%, and the thickness of the dopamine coating layer is 5 nanometers to 10 nanometers;

[0027] The zeolite powder has a fineness of 250 to 350 meshes. In addition to high-temperature calcination and microwave treatment, it is also subjected to acid modification treatment, soaked in a 2 mol / L hydrochloric acid solution for 1 to 2 hours, and then rinsed with clean water until neutral;

[0028] The specific surface area of ​​the slag powder is not less than 450 square meters / kilogram, and the activity index is not less than S95 level. In the ultrafine grinding process, a grinding aid with a mass ratio of 0.3% to 0.8% is added, and the grinding aid is a mixture of triethanolamine and ethylene glycol in a mass ratio of 2:1;

[0029] The ferroferric oxide in the magnetic adsorption particles is a nano-sized particle with a particle size of 20 nanometers to 50 nanometers, prepared by chemical co-precipitation, and the activated carbon is coconut shell activated carbon, which is subjected to high-temperature activation treatment, the activation temperature is 800° C. to 1000° C., and the treatment time is 2 hours to 3 hours;

[0030] The average particle size of the self-repairing microcapsules is 0.2 mm to 0.5 mm, the mass ratio of epoxy resin to curing agent in the core material is 3:1, and the curing agent is a polyamide curing agent.

[0031] Preferably, the crushing and screening process of the recycled slag aggregate adopts a multi-stage crushing and multi-stage screening combined process, firstly using a jaw crusher for coarse crushing, then using a cone crusher for crushing, and finally using an impact crusher for fine crushing, and the screening equipment uses a vibrating screen, and the screen apertures are 5 mm, 10 mm and 20 mm respectively;

[0032] In the preparation process of the magnesium-aluminum spinel micropowder in the cement, magnesium salt and aluminum salt are first dissolved in water according to a stoichiometric ratio, and then ammonia water or sodium hydroxide solution is added as a precipitant to carry out a precipitation reaction. After the reaction is completed, the precipitant is filtered, washed, dried and calcined to obtain the magnesium-aluminum spinel micropowder;

[0033] The carbon nanotubes in the silicon ash are pretreated before being added, the carbon nanotubes are dispersed in an organic solvent such as ethanol or acetone, and then a sodium dodecylbenzene sulfonate surfactant is added for ultrasonic treatment for 30 to 60 minutes;

[0034] The carbon fibers in the reinforcing fibers are subjected to surface oxidation treatment and then to surface coating treatment, wherein a specially prepared polymer coating material is evenly coated on the surface of the carbon fibers, and the coating thickness is 0.1 micrometer to 0.3 micrometer. The polymer coating material is composed of epoxy resin, polyurethane and silane coupling agent in a mass ratio of 4:3:1.

[0035] During the preparation process of the nano-scale water permeability promoter in the water permeability aid, a hydrothermal synthesis method is adopted to mix a silicon source, an aluminum source and a template agent in a certain proportion, react at a certain temperature and pressure, and after the reaction is completed, it is washed, dried and calcined to obtain a zeolite molecular sieve with a specific pore structure;

[0036] After the double surface modification treatment, the nano titanium dioxide is dried at a temperature of 80° C. to 100° C. for a drying time of 2 to 3 hours.

[0037] After the multi-stage activation treatment, the zeolite powder is subjected to quality inspection and performance evaluation to inspect its adsorption performance, ion exchange capacity and pore structure index;

[0038] After the slag powder is ultrafinely ground and doped with nano-alumina, an activity test is performed, and its activity is determined by a chemically combined water method or an intensity activity index method;

[0039] During the preparation of the magnetic adsorption particles, ferroferric oxide and activated carbon are mixed in proportion, polyvinyl alcohol or polyacrylic acid binder is added and stirred, and then dried and cured;

[0040] During the preparation process of the self-repairing microcapsules, an in-situ polymerization method is adopted to mix the urea-formaldehyde resin prepolymer and the core material, and then a polymerization reaction is carried out. After the reaction is completed, the self-repairing microcapsules are washed, dried and screened to obtain self-repairing microcapsules with uniform particle sizes.

[0041] Preferably, the method comprises the following steps:

[0042] S1. Preparation of recycled slag aggregate:

[0043] The construction waste of slag is initially crushed to remove impurities and large pieces of non-slag materials. During the initial crushing process, sorting equipment is used to automatically sort out metal, plastic and other impurities in the slag;

[0044] The slag after preliminary crushing is further finely crushed and screened to obtain recycled slag aggregates with different particle sizes. In the fine crushing process, a closed-circuit crushing system is used;

[0045] The recycled slag aggregate is placed in nano-silica sol for impregnation and strengthening treatment, and after the treatment is completed, the aggregate is taken out and dried for use, and then the dried aggregate is placed in a bio-based strengthening agent for secondary impregnation treatment, and after the treatment is completed, it is dried again;

[0046] S2. Raw material pretreatment:

[0047] Pre-treating cement, mixing cement with magnesium aluminum spinel micropowder and nano calcium hydroxide additive, and stirring with a high-speed mixer at a stirring speed of 500 to 800 revolutions per minute for a stirring time of 2 to 3 minutes;

[0048] Plasma modification treatment is performed on fly ash, the fly ash is placed in a plasma treatment device, and the treatment is performed according to a set treatment power and time, and the fly ash is taken out for standby use after the treatment is completed;

[0049] Pre-treating the silica ash, mixing the silica ash with the carbon nanotubes, and uniformly dispersing the silica ash with the carbon nanotubes by ultrasonic dispersion technology, wherein the ultrasonic frequency is 30 kHz to 50 kHz and the treatment time is 30 minutes to 60 minutes;

[0050] Pretreating the reinforcing fibers, mixing different types of reinforcing fibers in proportion, and then dispersing the mixed fibers in an aqueous solution containing a dispersant, wherein the amount of the dispersant is 0.5% to 1.5% of the fiber weight, and fully dispersing the fibers by combining high-speed stirring and ultrasonic-assisted dispersion, wherein the stirring speed is 1000 to 1500 rpm, the ultrasonic frequency is 40 kHz to 60 kHz, and the treatment time is 10 to 20 minutes;

[0051] Pre-treating the nano titanium dioxide, mixing the nano titanium dioxide in the proportion of anatase type and rutile type, and then treating it by using a double surface modification method, after the treatment, evenly dispersing it in water, and using ultrasonic dispersion technology to fully disperse it, the ultrasonic frequency is 40kHz to 60kHz, and the treatment time is 10 minutes to 15 minutes;

[0052] The zeolite powder is subjected to multi-stage activation treatment, which is carried out in the order of high-temperature calcination, microwave treatment, and acid modification. After the treatment is completed, quality inspection and performance evaluation are carried out;

[0053] The slag powder is subjected to ultrafine grinding treatment, the slag powder is mixed with additives such as nano-alumina, and ultrafine grinding equipment is used for grinding for 1 to 2 hours to ensure that the average particle size is no more than 5 microns;

[0054] To prepare magnetic adsorption particles, ferroferric oxide and activated carbon are mixed in proportion, a binder is added and stirred to form a uniform granular substance, and then dried and cured at a certain temperature, the drying temperature is 100° C. to 120° C., and the drying time is 1 hour to 2 hours;

[0055] The self-repairing microcapsules are prepared by an in-situ polymerization method. After the urea-formaldehyde resin prepolymer and the core material are mixed, a polymerization reaction is carried out under certain conditions. The reaction temperature is 60°C to 80°C and the reaction time is 2 hours to 3 hours. After the reaction is completed, the self-repairing microcapsules are washed, dried and screened to obtain self-repairing microcapsules with uniform particle size.

[0056] S3, raw material mixing:

[0057] Weigh the pretreated cement, fly ash, silica fume, zeolite powder, and slag powder according to weight, add them into a mixer, and stir at a speed of 35 to 55 rpm for 2.5 to 3.5 minutes;

[0058] S4, adding water and stirring step:

[0059] Add 62% to 72% of the total water consumption into the mixer, add a water reducing agent and a water permeability aid at the same time, stir at a speed of 85 to 105 rpm for 3.5 to 5.5 minutes, during the stirring process, use a temperature control system to control the water temperature within the range of 22° C. to 32° C., and add a retarder to the water, the amount of which is 0.1% to 0.3% of the weight of the cement;

[0060] S5. Aggregate addition:

[0061] Slowly add the treated recycled soil aggregate into the mixer and continue stirring for 3.5 to 5.5 minutes. During the process of adding the aggregate, use automatic feeding equipment to ensure the speed and uniformity of adding the aggregate;

[0062] S6, fiber dispersion addition:

[0063] Slowly add the pretreated reinforcing fibers into the mixer, and continue stirring at a speed of 55 to 75 rpm for 2.5 to 3.5 minutes. During the stirring process, use a fiber dispersion monitoring system to monitor the dispersion of the fibers in real time to ensure that the fibers are evenly distributed in the concrete.

[0064] S7. Addition of nanomaterials:

[0065] Slowly add the pretreated nano-titanium dioxide solution and magnetic adsorption particles into the mixer and continue stirring for 2 to 3 minutes. During the stirring process, use a magnetic stirrer to ensure uniform dispersion of the nano-materials.

[0066] S8, microcapsule addition:

[0067] Slowly add the prepared self-repairing microcapsules into the mixer and continue stirring for 1 to 2 minutes. During the process of adding the microcapsules, stir at a low speed to avoid the rupture of the microcapsules.

[0068] S9, discharging and forming:

[0069] The mixed concrete is discharged from the mixer and poured into the mold for molding. After molding, it is cured for no less than 7 days at a temperature of 22°C to 32°C and a relative humidity of no less than 90%. During the curing process, an intelligent curing system is used to monitor and control the curing environment in real time to ensure that the curing conditions meet the requirements.

[0070] (III) Beneficial technical effects

[0071] The present invention converts slag-type construction waste into recycled slag aggregate by finely processing it. A multi-stage crushing process combining jaw crusher, cone crusher and impact crusher and precise screening technology are adopted to make the particle size distribution of recycled slag aggregate reasonable. After enhanced treatment, it is used for concrete preparation. Every ton of slag-type construction waste processed can reduce about 0.5 cubic meters of landfill space, reducing the dependence on natural aggregate. At the same time, magnesium aluminum spinel powder and nano calcium hydroxide are added to cement, and slag powder is specially treated, so as to achieve optimal utilization of resources and cost reduction.

[0072] The present invention greatly improves the strength of concrete by adding specific substances to cement and rationally proportioning and treating the reinforcing fibers. For example, at 28 days of age, the compressive strength can reach no less than 30MPa, which is about 30% higher than that of traditional permeable concrete. Among them, the reinforcing fibers include polypropylene fibers, basalt fibers and carbon fibers in a mass ratio of 3:2:1 to form a mixed fiber, and the carbon fibers are surface oxidized and coated to make the flexural strength no less than 5MPa, which is about 40% higher than the traditional one, effectively reducing the risk of cracks and extending the service life.

[0073] The present invention adds nano-scale water permeability promoter (zeolite molecular sieve with special pore structure) to the water permeability aid, combines precise preparation process and stirring control, and makes the water permeability coefficient not less than 2.0 mm / s, which is about 40% higher than that of traditional permeable concrete. It can quickly infiltrate rainwater into the ground, relieve urban drainage pressure, reduce road surface waterlogging, and improve travel safety.

[0074] By adding self-repairing microcapsules, when cracks appear in the concrete, the microcapsules rupture and release repair materials. For cracks less than 2 mm in width, the self-repairing efficiency can reach more than 80%, reducing the cost and workload of later maintenance and extending the service life. Adding magnetic adsorption particles (composed of ferroferric oxide and activated carbon), the adsorption rate of common heavy metal ions is not less than 40%, and the adsorption rate of organic pollutants is also high, improving the quality of urban water environment. Using composite water reducers, the water reduction rate is increased to not less than 30%, the water-cement ratio is reduced, the working performance of concrete is improved, and its fluidity is increased by about 30%, reducing the difficulty and cost of construction, while improving the strength and durability of concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 It is a process diagram of concrete preparation process. DETAILED DESCRIPTION

[0076] Recycled slag aggregate: 850 to 1250 parts, wherein the recycled slag aggregate is obtained by crushing, screening and strengthening treatment of slag construction waste, wherein the particle size of 5 mm to 10 mm accounts for 42% to 52%, the particle size of 10 mm to 20 mm accounts for 32% to 42%, and the particle size of 20 mm to 30 mm accounts for 12% to 22%. In the strengthening treatment of the recycled slag aggregate, nano-silica sol is used for surface impregnation treatment, the impregnation time is 1.2 hours to 2.2 hours, the solid content of the nano-silica sol is 12% to 22%, and a bio-based strengthener is used for secondary impregnation treatment, the bio-based strengthener is composed of chitosan, sodium lignin sulfonate and sodium alginate in a weight ratio of 2:1:1, and the impregnation time is 0.5 hours to 1 hour;

[0077] Cement: 220 to 380 parts, wherein the cement is mixed with 5 to 10% by weight of magnesium-aluminum spinel powder, the particle size of which is 1 to 5 microns, which can effectively improve the early strength and crack resistance of the cement;

[0078] Fly ash: 60 to 110 parts. The fly ash is treated with plasma modification at a power of 10 kW to 20 kW for 10 to 20 minutes to enhance its surface activity and improve its binding force with other components.

[0079] Silica fume: 25 to 55 parts, with 3 to 8% by weight of carbon nanotubes added to the silica fume. The length of the carbon nanotubes is 10 to 30 microns, and the diameter is 5 to 10 nanometers, which can enhance the electrical and thermal conductivity of concrete, while improving its mechanical properties;

[0080] Water reducer: 4 to 9 parts. The water reducer is a composite water reducer composed of polycarboxylic acid high-performance water reducer, lignin sulfonate water reducer and β-cyclodextrin grafted modified water reducer in a mass ratio of 5:2:1, and the water reduction rate is not less than 30%;

[0081] Reinforcement fiber: 6 to 18 parts, fiber length is 12 mm to 25 mm. The reinforcement fiber includes a mixed fiber composed of polypropylene fiber, basalt fiber and carbon fiber in a mass ratio of 3:2:1. The carbon fiber is surface oxidized by soaking it in a 5 mol / L nitric acid solution for 1 to 2 hours, and then drying it at 80°C to 100°C to form rich oxygen-containing functional groups on its surface, thereby improving the bonding strength with the concrete matrix;

[0082] Water permeability aid: 3 to 7 parts, the water permeability aid is composed of the following raw materials in parts by weight: 1.5 to 3.5 parts of organic silane coupling agent, 1.5 to 3.5 parts of surfactant, and 1 to 2 parts of a new type of nano-scale water permeability promoter. The nano-scale water permeability promoter is a zeolite molecular sieve with a special pore structure, with a pore size of 2 nanometers to 5 nanometers, which can form an efficient water permeable channel in the concrete;

[0083] Nano titanium dioxide: 4 to 9 parts. Nano titanium dioxide is a mixture of anatase and rutile in a mass ratio of 3:2. The particle size is 8 to 25 nanometers. It has undergone double surface modification treatment, first using a silane coupling agent for surface grafting treatment, and then using dopamine for coating, so that it has better dispersibility and photocatalytic performance;

[0084] Zeolite powder: 12 to 35 parts. The zeolite powder undergoes multi-stage activation treatment, first calcined at a high temperature of 400 to 600°C for 2 to 3 hours, and then treated at a microwave power of 500 to 800 W for 5 to 10 minutes, so that its pore structure is more developed and the adsorption performance is significantly enhanced;

[0085] Slag powder: 35 to 65 parts. The slag powder is ultra-finely ground to a particle size of no more than 5 microns, and 2 to 5% by weight of nano-alumina is added to the powder. The particle size of the nano-alumina is 10 to 20 nanometers, which can further improve the activity of the slag powder and the strength of the concrete.

[0086] Magnetic adsorption particles: 5 to 10 parts. The magnetic adsorption particles are composed of ferroferric oxide and activated carbon in a mass ratio of 3:2. The particle size is 0.5 mm to 2 mm. They can effectively adsorb heavy metal ions and organic pollutants in water and improve the environmental performance of concrete.

[0087] Self-repairing microcapsules: 3 to 8 parts. The wall material of the self-repairing microcapsules is urea-formaldehyde resin, and the core material is a mixture of epoxy resin and curing agent. When cracks appear in the concrete, the microcapsules rupture and release the repair material to achieve automatic repair function.

[0088] Example 1

[0089] S1. Preparation of recycled slag aggregate:

[0090] The slag-type construction waste is initially crushed to remove impurities and large pieces of non-slag materials. During the initial crushing process, sorting equipment is used to automatically sort out metal, plastic and other impurities in the slag.

[0091] The slag after preliminary crushing is further finely crushed and screened, and a multi-stage crushing and multi-stage screening combined process is adopted. It is first coarsely crushed by a jaw crusher, then medium crushed by a cone crusher, and finally finely crushed by an impact crusher. The screening equipment uses a vibrating screen with screen apertures of 5 mm, 10 mm and 20 mm respectively. Through the combined use of screens with different apertures, accurate grading of aggregates is achieved, and recycled slag aggregates of different particle size ranges are obtained. In the fine crushing process, a closed-loop crushing system is adopted.

[0092] The recycled slag aggregate is placed in nano-silica sol for impregnation and strengthening treatment. After the treatment, it is taken out and dried for use. Then the dried aggregate is placed in a bio-based strengthener for secondary impregnation treatment. After the treatment, it is dried again.

[0093] S2. Raw material pretreatment:

[0094] The cement is pretreated. The cement is silicate cement with a strength grade of not less than 42.5. 300 kg of cement is mixed with 30 kg of magnesium aluminum spinel powder and 3 kg of nano calcium hydroxide additive. A high-speed mixer is used for stirring at a speed of 800 rpm for 2 to 3 minutes.

[0095] In the preparation process of the magnesium-aluminum spinel micropowder in the cement, magnesium salt and aluminum salt are first dissolved in water according to a stoichiometric ratio, and then ammonia water or sodium hydroxide solution is added as a precipitant to carry out a precipitation reaction. After the reaction is completed, the magnesium-aluminum spinel micropowder is filtered, washed, dried and calcined to obtain the magnesium-aluminum spinel micropowder.

[0096] 100 kg of fly ash was subjected to plasma modification treatment. The fly ash was placed in a plasma treatment device with a treatment power of 15 kW and a treatment time of 20 minutes. After the treatment was completed, the fly ash was taken out for use.

[0097] The silica ash was pretreated by mixing 30 kg of silica ash with 1.5 kg of carbon nanotubes and uniformly dispersing them in the silica ash using ultrasonic dispersion technology. The ultrasonic frequency was 50 kHz and the treatment time was 60 minutes.

[0098] The carbon nanotubes in the silicon ash are pretreated before being added, the carbon nanotubes are dispersed in an ethanol organic solvent, and then a sodium dodecylbenzene sulfonate surfactant is added for ultrasonic treatment for 60 minutes to make them uniformly dispersed in the silicon ash.

[0099] 15 kg of reinforcing fibers were pretreated by mixing polypropylene fibers, basalt fibers and carbon fibers in a mass ratio of 3:2:1. The mixed fibers were then dispersed in an aqueous solution containing a dispersant in an amount of 0.15 kg. High-speed stirring and ultrasonic-assisted dispersion were combined to fully disperse the fibers. The stirring speed was 1500 rpm, the ultrasonic frequency was 50 kHz, and the treatment time was 15 minutes.

[0100] The polypropylene fiber in the reinforcing fiber is a modified polypropylene fiber, and an acrylic copolymer is grafted on its surface to improve the fiber's alkali resistance and bonding performance with concrete. The basalt fiber is treated with a silane coupling agent on the surface, with a treatment solution concentration of 5% and a treatment time of 1 hour.

[0101] The carbon fibers in the reinforcing fibers are subjected to surface oxidation treatment by soaking them in a nitric acid solution with a concentration of 5 mol / L for 2 hours and then drying them at 100°C to form abundant oxygen-containing functional groups on their surface, thereby improving the bonding strength with the concrete matrix. Surface coating treatment is also performed by evenly coating a special polymer coating material on the surface of the carbon fibers with a coating thickness of 0.1 to 0.3 microns. The polymer coating material is composed of epoxy resin, polyurethane and silane coupling agent in a mass ratio of 4:3:1.

[0102] 5 kg of nano titanium dioxide was pretreated by mixing the nano titanium dioxide in a ratio of 3 kg of anatase type and 2 kg of rutile type, and then treated by a double surface modification method. First, the surface was grafted with a silane coupling agent γ-aminopropyltriethoxysilane, and then coated with dopamine. After the treatment, it was evenly dispersed in water and fully dispersed by ultrasonic dispersion technology. The ultrasonic frequency was 50 kHz and the treatment time was 15 minutes.

[0103] After the double surface modification treatment, the nano titanium dioxide is dried at a temperature of 100° C. for 2 hours to ensure that the modified nano titanium dioxide has good stability and dispersibility.

[0104] 25 kg of zeolite powder was subjected to a multi-stage activation treatment. It was first calcined at a high temperature of 500°C for 3 hours, then treated at a microwave power of 600 W for 8 minutes, soaked in a 2 mol / L hydrochloric acid solution for 2 hours, and then rinsed with clean water until neutral. After the treatment was completed, quality inspection and performance evaluation were carried out.

[0105] The slag powder was ultrafinely ground by mixing 50 kg of slag powder with 2.5 kg of nano-alumina and 0.25 kg of a grinding aid, which was a mixture of triethanolamine and ethylene glycol in a mass ratio of 2:1. The powder was ground using an ultrafine grinding device for 1.5 hours to ensure that the average particle size was no greater than 5 microns.

[0106] To prepare magnetic adsorption particles, 6 kg of ferrosoferric oxide and 4 kg of activated carbon were mixed, where the activated carbon was coconut shell activated carbon. After high-temperature activation treatment at 1000°C for 2 hours, 0.5 kg of binder polyvinyl alcohol was added and stirred to form a uniform granular substance, which was then dried and cured at a certain temperature at 120°C for 2 hours.

[0107] Self-healing microcapsules were prepared by in-situ polymerization. 2 kg of urea-formaldehyde resin prepolymer and 6 kg of core material were mixed. The mass ratio of epoxy resin to curing agent in the core material was 3:1. The curing agent was polyamide 650. The polymerization reaction was carried out under certain conditions. The reaction temperature was 80 ° C and the reaction time was 3 hours. After the reaction was completed, the self-healing microcapsules with uniform particle size were obtained after washing, drying and screening.

[0108] S3, raw material mixing:

[0109] 300 kg of pretreated cement, 100 kg of fly ash, 30 kg of silica fume, 25 kg of zeolite powder and 50 kg of slag powder were weighed by weight, added into a mixer, and stirred at a speed of 55 rpm for 3 minutes.

[0110] S4, adding water and stirring step:

[0111] Add water accounting for 62% to 72% of the total water consumption into the mixer, and add 8kg of water reducer and 6kg of water permeability aid at the same time. The water reducer is composed of polycarboxylic acid high-performance water reducer, lignin sulfonate water reducer and β-cyclodextrin grafted modified water reducer in a mass ratio of 5:2:1. The water permeability aid is composed of the following raw materials in parts by weight: 2kg of organic silane coupling agent, 2kg of surfactant, and 2kg of a new type of nano-scale water permeability promoter. Stir at a speed of 100 rpm for 4 minutes. During the stirring process, a temperature control system is used to control the water temperature within the range of 22°C to 32°C, and a retarder is added to the water. The amount of the retarder is 3kg.

[0112] The preparation method of the β-cyclodextrin grafted modified water reducer in the water reducer is: grafting β-cyclodextrin with acrylic acid under alkaline conditions with a pH value of 9 to 11, the reaction temperature is 60° C., the reaction time is 4 hours, and then compounding with a polycarboxylic acid high-performance water reducer and a lignin sulfonate water reducer.

[0113] During the preparation process of the nano-scale water permeability promoter in the water permeability aid, a hydrothermal synthesis method is adopted to mix a silicon source, an aluminum source and a template agent in a certain proportion, react at a certain temperature and pressure, and after the reaction is completed, it is washed, dried and calcined to obtain a zeolite molecular sieve with a specific pore structure.

[0114] S5. Aggregate addition:

[0115] Slowly add the processed recycled slag aggregate into the mixer and continue stirring for 5 minutes. During the process of adding the aggregate, use automatic feeding equipment to ensure the speed and uniformity of adding the aggregate.

[0116] S6, fiber dispersion addition:

[0117] Slowly add the pretreated reinforcing fibers into the mixer and continue stirring at a speed of 55 to 75 rpm for 2.5 to 3.5 minutes. During the stirring process, a fiber dispersion monitoring system is used to monitor the dispersion of the fibers in real time to ensure that the fibers are evenly distributed in the concrete.

[0118] S7. Addition of nanomaterials:

[0119] The pretreated nano titanium dioxide solution and magnetic adsorption particles are slowly added into the mixer and stirred for 2 to 3 minutes. During the stirring process, a magnetic stirrer is used to ensure uniform dispersion of the nanomaterials.

[0120] S8, microcapsule addition:

[0121] Slowly add the prepared self-repairing microcapsules into the mixer and continue stirring for 1 to 2 minutes. During the process of adding the microcapsules, stir at a low speed to avoid rupture of the microcapsules.

[0122] S9, discharging and forming:

[0123] The mixed concrete is discharged from the mixer and poured into the mold for molding. After molding, it is cured for no less than 7 days at a temperature of 22°C to 32°C and a relative humidity of no less than 90%. During the curing process, an intelligent curing system is used to monitor and control the curing environment in real time to ensure that the curing conditions meet the requirements.

[0124] Comparative Example 1: No reinforcing fiber was added, and the rest of the process was the same as in Example 1.

[0125] Comparative Example 2: No water permeability aid was added, and the rest of the process was the same as in Example 1.

[0126] Comparative Example 3: No self-repairing capsules were added, and the rest of the process was the same as in Example 1.

[0127] Comparative Example 4: No water reducing agent was added, and the rest of the process was the same as in Example 1.

[0128] Performance Testing:

[0129] 1. The concrete of Example 1 and Comparative Example 1 were tested according to GB / T 50081-2019. The test results are shown in Table 1;

[0130] Table 1

[0131] Group 28d compressive strength (MPa) 28d flexural strength (MPa) Example 1 35 5.3 Comparative Example 1 25 4.4

[0132] It can be seen from Table 1 that the concrete prepared in Example 1 has better compressive strength and flexural strength.

[0133] 2. According to the "Test Method for Water Permeability Coefficient of Permeable Cement Concrete", the water permeability of Example 1 and Comparative Example 2 was tested and the water permeability coefficient was calculated. The results are shown in Table 2;

[0134] Table 2

[0135] Group Water permeability coefficient (mm / s) Example 1 2.3 Comparative Example 2 1.8

[0136] It can be seen from Table 2 that the water permeability coefficient of the concrete prepared in Example 1 is greater than that of Comparative Example 2, and the water permeability of Example 1 is higher.

[0137] 3. Example 1 and Comparative Example 3 were made into concrete slabs of 200 mm × 200 mm × 30 mm, and cracks were generated on their surfaces by compression and shearing operations. The self-repairing effect was observed. The results are shown in Table 3;

[0138] Table 3

[0139] Group Self-repair effect Example 1 Complete repair of cracks less than 2mm in width Comparative Example 3 No repair effect

[0140] It can be seen from Table 3 that Example 1 has a good self-repairing effect.

[0141] 4. The water reduction rate of Example 1 and Comparative Example 4 was tested according to GB / T 8077-2012. The results are shown in Table 4;

[0142] Table 4

[0143] Group Water reduction rate (%) Example 1 32 Comparative Example 4 12

[0144] It can be seen from Table 4 that the water reduction rate of Example 1 is higher, which effectively improves the working performance of concrete.

[0145] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A permeable concrete recycled from construction waste, characterized in that: It is composed of the following components in parts by weight: Recycled slag aggregate: 850 to 1250 parts, wherein the recycled slag aggregate is obtained by crushing, screening and strengthening treatment of slag construction waste, wherein the particle size of 5 mm to 10 mm accounts for 42% to 52%, the particle size of 10 mm to 20 mm accounts for 32% to 42%, and the particle size of 20 mm to 30 mm accounts for 12% to 22%. In the strengthening treatment of the recycled slag aggregate, nano-silica sol is used for surface impregnation treatment, the impregnation time is 1.2 hours to 2.2 hours, the solid content of the nano-silica sol is 12% to 22%, and a bio-based strengthener is used for secondary impregnation treatment, the bio-based strengthener is composed of chitosan, sodium lignin sulfonate and sodium alginate in a weight ratio of 2:1:1, and the impregnation time is 0.5 hours to 1 hour; Cement: 220 to 380 parts, wherein the cement is mixed with 5 to 10% by weight of magnesium-aluminum spinel powder, and the particle size of the magnesium-aluminum spinel powder is 1 to 5 microns; Fly ash: 60 to 110 parts, the fly ash is treated by plasma modification, the treatment power is 10 kW to 20 kW, and the treatment time is 10 to 20 minutes; Silica fume: 25 to 55 parts, wherein 3 to 8% by weight of carbon nanotubes are added to the silica fume, and the length of the carbon nanotubes is 10 to 30 microns, and the diameter is 5 to 10 nanometers; Water reducer: 4 to 9 parts. The water reducer is a composite water reducer composed of polycarboxylic acid high-performance water reducer, lignin sulfonate water reducer and β-cyclodextrin grafted modified water reducer in a mass ratio of 5:2:

1. Reinforcement fiber: 6 to 18 parts, fiber length is 12 mm to 25 mm, the reinforcement fiber includes a mixed fiber composed of polypropylene fiber, basalt fiber and carbon fiber in a mass ratio of 3:2:1, and the carbon fiber is surface oxidized by immersing it in a nitric acid solution with a concentration of 5 mol / L for 1 to 2 hours, and then drying it at 80°C to 100°C; Water permeability enhancer: 3 to 7 parts, the water permeability enhancer is composed of the following raw materials in parts by weight: 1.5 to 3.5 parts of an organic silane coupling agent, 1.5 to 3.5 parts of a surfactant, and 1 to 2 parts of a new type of nano-scale water permeability enhancer, the nano-scale water permeability enhancer is a zeolite molecular sieve with a special pore structure, and its pore size is 2 nanometers to 5 nanometers; Nano titanium dioxide: 4 to 9 parts. Nano titanium dioxide is a mixture of anatase and rutile in a mass ratio of 3:

2. The particle size is 8 to 25 nanometers. It has undergone double surface modification treatment, first using a silane coupling agent for surface grafting treatment, and then using dopamine for coating; Zeolite powder: 12 to 35 parts, the zeolite powder undergoes multi-stage activation treatment, first calcined at a high temperature of 400 to 600°C for 2 to 3 hours, and then treated at a microwave power of 500 to 800 W for 5 to 10 minutes; Slag powder: 35 to 65 parts, the slag powder is ultra-finely ground to a mean particle size of no more than 5 microns, and 2 to 5% by weight of nano-alumina is added thereto, the particle size of the nano-alumina being 10 to 20 nanometers; Magnetic adsorption particles: 5 to 10 parts, the magnetic adsorption particles are composed of ferroferric oxide and activated carbon in a mass ratio of 3:2, and the particle size is 0.5 mm to 2 mm; Self-repairing microcapsules: 3 to 8 parts. The wall material of the self-repairing microcapsules is urea-formaldehyde resin, and the core material is a mixture of epoxy resin and curing agent.

2. The permeable concrete recycled from construction waste of muck and earth according to claim 1, characterized in that: The cement is silicate cement or ordinary silicate cement with a strength grade of not less than 42.5, and nano calcium hydroxide accounting for 0.5% to 1.5% by weight is added to the cement, and the particle size of the nano calcium hydroxide is 20 nanometers to 50 nanometers; The polypropylene fiber in the reinforcing fiber is a modified polypropylene fiber, and an acrylic copolymer is grafted on its surface; the basalt fiber is treated with a surface silane coupling agent, the concentration of the treatment solution is 3% to 5%, and the treatment time is 0.5 hour to 1 hour; The preparation method of the β-cyclodextrin grafted modified water reducer in the water reducer is: grafting β-cyclodextrin with acrylic acid under alkaline conditions with a pH value of 9 to 11, the reaction temperature is 50° C. to 70° C., the reaction time is 3 hours to 5 hours, and then compounding with a polycarboxylic acid high-performance water reducer and a lignin sulfonate water reducer; The silane coupling agent grafted on the surface of the nano titanium dioxide is γ-aminopropyltriethoxysilane, the grafting rate is not less than 80%, and the thickness of the dopamine coating layer is 5 nanometers to 10 nanometers; The zeolite powder has a fineness of 250 to 350 meshes. In addition to high-temperature calcination and microwave treatment, it is also subjected to acid modification treatment, soaked in a 2 mol / L hydrochloric acid solution for 1 to 2 hours, and then rinsed with clean water until neutral; The specific surface area of ​​the slag powder is not less than 450 square meters / kilogram, and the activity index is not less than S95 level. In the ultrafine grinding process, a grinding aid with a mass ratio of 0.3% to 0.8% is added, and the grinding aid is a mixture of triethanolamine and ethylene glycol in a mass ratio of 2:1; The ferroferric oxide in the magnetic adsorption particles is a nano-sized particle with a particle size of 20 nanometers to 50 nanometers, prepared by chemical co-precipitation, and the activated carbon is coconut shell activated carbon, which is subjected to high-temperature activation treatment, the activation temperature is 800° C. to 1000° C., and the treatment time is 2 hours to 3 hours; The average particle size of the self-repairing microcapsules is 0.2 mm to 0.5 mm, the mass ratio of epoxy resin to curing agent in the core material is 3:1, and the curing agent is a polyamide curing agent.

3. The permeable concrete recycled from construction waste of muck and soil according to claim 1, characterized in that: The crushing and screening process of the recycled slag aggregate adopts a multi-stage crushing and multi-stage screening combined process, firstly using a jaw crusher for coarse crushing, then using a cone crusher for crushing, and finally using an impact crusher for fine crushing, and the screening equipment uses a vibrating screen with screen apertures of 5 mm, 10 mm and 20 mm respectively; In the preparation process of the magnesium-aluminum spinel micropowder in the cement, magnesium salt and aluminum salt are first dissolved in water according to a stoichiometric ratio, and then ammonia water or sodium hydroxide solution is added as a precipitant to carry out a precipitation reaction. After the reaction is completed, the precipitant is filtered, washed, dried and calcined to obtain the magnesium-aluminum spinel micropowder; The carbon nanotubes in the silicon ash are pretreated before being added, the carbon nanotubes are dispersed in an organic solvent such as ethanol or acetone, and then a sodium dodecylbenzene sulfonate surfactant is added for ultrasonic treatment for 30 to 60 minutes; The carbon fibers in the reinforcing fibers are subjected to surface oxidation treatment and then to surface coating treatment, wherein a specially prepared polymer coating material is evenly coated on the surface of the carbon fibers, and the coating thickness is 0.1 micrometer to 0.3 micrometer. The polymer coating material is composed of epoxy resin, polyurethane and silane coupling agent in a mass ratio of 4:3:

1. During the preparation process of the nano-scale water permeability promoter in the water permeability aid, a hydrothermal synthesis method is adopted to mix a silicon source, an aluminum source and a template agent in a certain proportion, react at a certain temperature and pressure, and after the reaction is completed, it is washed, dried and calcined to obtain a zeolite molecular sieve with a specific pore structure; After the double surface modification treatment, the nano titanium dioxide is dried at a temperature of 80° C. to 100° C. for a drying time of 2 to 3 hours. During the preparation of the magnetic adsorption particles, ferroferric oxide and activated carbon are mixed in proportion, polyvinyl alcohol or polyacrylic acid binder is added and stirred, and then dried and cured; During the preparation process of the self-repairing microcapsules, an in-situ polymerization method is adopted to mix the urea-formaldehyde resin prepolymer and the core material, and then a polymerization reaction is carried out. After the reaction is completed, the self-repairing microcapsules are washed, dried and screened to obtain self-repairing microcapsules with uniform particle sizes.

4. The permeable concrete recycled from construction waste according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Preparation of recycled slag aggregate: The construction waste of slag is initially crushed to remove impurities and large pieces of non-slag materials. During the initial crushing process, sorting equipment is used to automatically sort out metal, plastic and other impurities in the slag; The slag after preliminary crushing is further finely crushed and screened to obtain recycled slag aggregates with different particle sizes. In the fine crushing process, a closed-circuit crushing system is used; The recycled slag aggregate is placed in nano-silica sol for impregnation and strengthening treatment, and after the treatment is completed, the aggregate is taken out and dried for use, and then the dried aggregate is placed in a bio-based strengthening agent for secondary impregnation treatment, and after the treatment is completed, it is dried again; S2. Raw material pretreatment: Pre-treating cement, mixing cement with magnesium aluminum spinel micropowder and nano calcium hydroxide additive, and stirring with a high-speed mixer at a stirring speed of 500 to 800 revolutions per minute for a stirring time of 2 to 3 minutes; Plasma modification treatment is performed on fly ash, the fly ash is placed in a plasma treatment device, and the treatment is performed according to a set treatment power and time, and the fly ash is taken out for standby use after the treatment is completed; Pre-treating the silica ash, mixing the silica ash with the carbon nanotubes, and uniformly dispersing the silica ash with the carbon nanotubes by ultrasonic dispersion technology, wherein the ultrasonic frequency is 30 kHz to 50 kHz and the treatment time is 30 minutes to 60 minutes; Pretreating the reinforcing fibers, mixing different types of reinforcing fibers in proportion, and then dispersing the mixed fibers in an aqueous solution containing a dispersant, wherein the amount of the dispersant is 0.5% to 1.5% of the fiber weight, and fully dispersing the fibers by combining high-speed stirring and ultrasonic-assisted dispersion, wherein the stirring speed is 1000 to 1500 rpm, the ultrasonic frequency is 40 kHz to 60 kHz, and the treatment time is 10 to 20 minutes; Pre-treating the nano titanium dioxide, mixing the nano titanium dioxide in the proportion of anatase type and rutile type, and then treating it by using a double surface modification method, after the treatment, evenly dispersing it in water, and using ultrasonic dispersion technology to fully disperse it, the ultrasonic frequency is 40kHz to 60kHz, and the treatment time is 10 minutes to 15 minutes; The zeolite powder is subjected to multi-stage activation treatment, which is carried out in the order of high-temperature calcination, microwave treatment, and acid modification. After the treatment is completed, quality inspection and performance evaluation are carried out; The slag powder is subjected to ultrafine grinding treatment, the slag powder is mixed with additives such as nano-alumina, and ultrafine grinding equipment is used for grinding for 1 to 2 hours to ensure that the average particle size is no more than 5 microns; To prepare magnetic adsorption particles, ferroferric oxide and activated carbon are mixed in proportion, a binder is added and stirred to form a uniform granular substance, and then dried and cured at a certain temperature, the drying temperature is 100° C. to 120° C., and the drying time is 1 hour to 2 hours; The self-repairing microcapsules are prepared by an in-situ polymerization method. After the urea-formaldehyde resin prepolymer and the core material are mixed, a polymerization reaction is carried out under certain conditions. The reaction temperature is 60°C to 80°C and the reaction time is 2 hours to 3 hours. After the reaction is completed, the self-repairing microcapsules are washed, dried and screened to obtain self-repairing microcapsules with uniform particle size. S3, raw material mixing: Weigh the pretreated cement, fly ash, silica fume, zeolite powder, and slag powder according to weight, add them into a mixer, and stir at a speed of 35 to 55 rpm for 2.5 to 3.5 minutes; S4, adding water and stirring step: Add 62% to 72% of the total water consumption into the mixer, add a water reducing agent and a water permeability aid at the same time, stir at a speed of 85 to 105 rpm for 3.5 to 5.5 minutes, during the stirring process, use a temperature control system to control the water temperature within the range of 22° C. to 32° C., and add a retarder to the water, the amount of which is 0.1% to 0.3% of the weight of the cement; S5. Aggregate addition: Slowly add the treated recycled soil aggregate into the mixer and continue stirring for 3.5 to 5.5 minutes. During the process of adding the aggregate, use automatic feeding equipment to ensure the speed and uniformity of adding the aggregate; S6, fiber dispersion addition: Slowly add the pretreated reinforcing fibers into the mixer, and continue stirring at a speed of 55 to 75 rpm for 2.5 to 3.5 minutes. During the stirring process, use a fiber dispersion monitoring system to monitor the dispersion of the fibers in real time to ensure that the fibers are evenly distributed in the concrete. S7. Addition of nanomaterials: Slowly add the pretreated nano-titanium dioxide solution and magnetic adsorption particles into the mixer and continue stirring for 2 to 3 minutes. During the stirring process, use a magnetic stirrer to ensure uniform dispersion of the nano-materials. S8, microcapsule addition: Slowly add the prepared self-repairing microcapsules into the mixer and continue stirring for 1 to 2 minutes. During the process of adding the microcapsules, stir at a low speed to avoid the rupture of the microcapsules. S9, discharging and forming: The mixed concrete is discharged from the mixer and poured into the mold for molding. After molding, it is cured for no less than 7 days at a temperature of 22°C to 32°C and a relative humidity of no less than 90%. During the curing process, an intelligent curing system is used to monitor and control the curing environment in real time to ensure that the curing conditions meet the requirements.

Citation Information

Patent Citations

  • Method for making river shore-based root stones by utilizing Yellow River silt and construction dregs

    CN103979889A

  • High-porosity high-permeability type double-layer permeable floor tile

    CN105367019A

  • Foamed element and preparation method thereof

    CN109232018A

Cited By

  • Highway permeable anti-crack concrete and preparation method thereof

    CN120423893A

  • Semi-rigid base material containing construction waste and preparation method thereof

    CN120864834A

  • Low-adsorption high-flowability gasified slag-based cement admixture and preparation method thereof

    CN122277137A

  • Construction waste doped fiber reinforced curing agent aggregate laying process

    CN122327590A